Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ana.26267
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation

Abstract: Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged ≥85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged ≥85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all‐cause death. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Of note, in our study the lower hazard for the composite outcome with both DOAC regimens as opposed to VKA seemed to be mainly driven by death, consistent with prior observational studies comparing DOAC versus VKA in AF patients with recent stroke. 6,7,28 More importantly and as a novelty, our study showed that the performance of QD versus BID DOAC with regards to the composite outcome did not differ upon direct comparison among AF patients with a recent stroke. While a number of observational studies previously compared DOAC directly to one another yielding somewhat inconsistent results, [32][33][34][35][36][37] none focused on patients with recent stroke nor conducted comparisons of the QD versus BID DOAC regimen.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Of note, in our study the lower hazard for the composite outcome with both DOAC regimens as opposed to VKA seemed to be mainly driven by death, consistent with prior observational studies comparing DOAC versus VKA in AF patients with recent stroke. 6,7,28 More importantly and as a novelty, our study showed that the performance of QD versus BID DOAC with regards to the composite outcome did not differ upon direct comparison among AF patients with a recent stroke. While a number of observational studies previously compared DOAC directly to one another yielding somewhat inconsistent results, [32][33][34][35][36][37] none focused on patients with recent stroke nor conducted comparisons of the QD versus BID DOAC regimen.…”
Section: Discussionmentioning
confidence: 61%
“…The primary outcome was the time to occurrence of the composite of recurrent ischemic stroke, major bleeding, and all-cause death, in accordance with prior research. [5][6][7] Secondary outcomes were the time to occurrence of each of these outcomes separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 92 ] Polymeris et al, in a multi-centre prospective cohort study, investigated the safety and efficacy of DOACs in comparison to warfarin in AF patients aged ≥ 85 years after a recent stroke (< 3 months). The study concluded that DOACs were associated with a lower risk of the composite outcome of recurrent ischemic stroke, intracranial haemorrhage, and all-cause mortality in patients with AF and recent ischemic stroke, independent of age [ 93 ].…”
Section: Eligibility For Doacs Therapy In Other Clinical Indicationsmentioning
confidence: 99%